Culture and associativity of MYPES manufacturing textile products in the Tacna city, Peru 2022 - Acosta Hinojosa, Justiniano David (2022)
Corporate Culture and Associativity represent very useful topics for the SME sector, currently they are alternative tools that can contribute to its growth and solve external events that contract its activity. In this sense, the objective of the research was to determine the relationship between culture and the process of associativity of the SME for the manufacture of textile products in the Tacna city, Peru 2021, it was taken into account that the textile sector comprises a large participation of SME in the locality. The population corresponds to 305 active SME, the study is descriptive - correlational and the design is non-experimental and cross-sectional. A 40-item questionnaire was applied taking into account the study variables, their dimensions and indicators. The research hypotheses had to do with the Culture variable, its dimensions: Norms, Customs, Values, Beliefs and Traditions, and the relationship they present with business association. It was concluded by stating that Culture has a moderate level relationship with the Associativity of the SME of manufacturing textile products in the Tacna city. In addition, the Beliefs present a high relationship with the Associativity of the textile SME of Tacna.